Deictic shifts in fiction translation: Evidence of a more marked perspective in the translated narrative - Abualadas, Othman (Universitas Pendidikan Indonesia, 2019)
This paper explores deictic shifts in fiction translation. It studies how deictic shifts affect the spatial-temporal and psychological point of view in four Arabic translations of Jane Eyre and A Farewell to Arms. The study reveals a tendency in translation to (i) use more spatial and temporal deixis, (ii) use more proximal than distal forms and (ii) use forms that are more marked for emotional space than physical space. This points to a translated narrative with a more emphasized spatial-temporal dimension, higher emotional proximity and empathy, and more marked psychological perspectives and voices. These shifts reposition the narrator and the other speaking characters. Based on the textual data, these shifts are best seen as traces of translators’ interpretive work and their second materialization of the original voices; the traces of the translators’ efforts to re-contextualize the original story based on their mental representation of the original perspectives.